Myeloid-Derived Suppressor Cells Promote the Progression of Primary Membranous Nephropathy by Enhancing Th17 Response - Li, Huimin; Wu, Hao; Guo, Qiaoyan; Yu, Hongyu; Xu, Ying; Yu, Jinyu; Wang, Zhongkun; Yi, Huanfa (Frontiers in Immunology, 2020)
Several studies have confirmed that the myeloid-derived suppressor cells (MDSCs) are closely associated with autoimmune diseases, but their exact role in these processes remains largely unclear. Here, we investigated the role MDSCs in patients with primary membranous nephropathy (PMN). Compared to healthy controls (HCs), PMN patients showed significantly increased number of HLA-DR−CD11b+CD33+ MDSCs in the peripheral blood, including both CD14+CD66b− monocytic and CD14−CD66b+ granulocytic MDSCs. The frequency of MDSCs was positively correlated with the level of serum anti-phospholipase A2 receptor (anti-PLA2R), 24-h urine protein quantification, and disease activity in PMN patients. Consistently, enhanced T helper 2 (Th2) and T helper 17 (Th17) immune responses were positively associated with plasma anti-PLA2R levels, 24-h urine protein quantification, and the disease activity in PMN patients. Moreover, compared to HCs, MDSCs from PMN patients exhibited significantly elevated arginase-1 (ARG-1) production and increased potential to promote Th17 differentiation in vitro in an ARG-1–dependent manner. This study directly demonstrates a pathogenic role for MDSCs in human PMN and provides a molecular mechanism for the pathogenesis of PMN. Our data show that MDSCs may promote PMN disease progression mainly by enhancing Th17 response. Therefore, MDSCs may be an important diagnostic, therapeutic, and prognostic marker for PMN diseases.